Impact of Antimalarial Treatment and Chemoprevention on the Drug Sensitivity of Malaria Parasites Isolated from Ugandan Children - Tumwebaze, Patrick; Conrad, Melissa D.; Walakira, Andrew; LeClair, Norbert; Byaruhanga, Oswald; Nakazibwe, Christine; Okiring, Jaffer; Kakuru, Abel; Bigira, Victor; Kapisi, James; Kamya, Moses R.; Greenhouse, Bryan; et al. (Antimicrobial agents and chemotherapy, 2015)
Changing treatment practices may be selecting for changes in the drug sensitivity of malaria parasites. We characterized ex vivo drug sensitivity and parasite polymorphisms associated with sensitivity in 459 Plasmodium falciparum samples obtained from subjects enrolled in two clinical trials in Tororo, Uganda, from 2010 to 2013. Sensitivities to chloroquine and monodesethylamodiaquine varied widely; sensitivities to quinine, dihydroartemisinin, lumefantrine, and piperaquine were generally good. Associations between ex vivo drug sensitivity and parasite polymorphisms included decreased chloroquine and monodesethylamodiaquine sensitivity and increased lumefantrine and piperaquine sensitivity with pfcrt 76T, as well as increased lumefantrine sensitivity with pfmdr1 86Y, Y184, and 1246Y. Over time, ex vivo sensitivity decreased for lumefantrine and piperaquine and increased for chloroquine, the prevalences of pfcrt K76 and pfmdr1 N86 and D1246 increased, and the prevalences of pfdhfr and pfdhps polymorphisms associated with antifolate resistance were unchanged. In recurrent infections, recent prior treatment with artemether-lumefantrine was associated with decreased ex vivo lumefantrine sensitivity and increased prevalence of pfcrt K76 and pfmdr1 N86, 184F, and D1246. In children assigned chemoprevention with monthly dihydroartemisinin-piperaquine with documented circulating piperaquine, breakthrough infections had increased the prevalence of pfmdr1 86Y and 1246Y compared to untreated controls. The noted impacts of therapy and chemoprevention on parasite polymorphisms remained significant in multivariate analysis correcting for calendar time. Overall, changes in parasite sensitivity were consistent with altered selective pressures due to changing treatment practices in Uganda. These changes may threaten the antimalarial treatment and preventive efficacies of artemether-lumefantrine and dihydroartemisinin-piperaquine, respectively.